My best friend's girl - Koomson, Dorothy (New York : Bantam Dell, 2008)
Kamryn Matika faces the biggest challenge of her life when Adele Brannon, a college friend who ruined their relationship by sleeping with Kamryn's fiance, Nate, calls and asks her to adopt her five-year-old daughter, Tegan, a child Nate does not even know exists.
"A Bantam Discovery book"--T.p. verso.
Adult
Adult
Publisher's Weekly
Keywords: Female friendship -- Fiction; Terminally ill -- Fiction; Adoption -- Fiction; Forgiveness -- Fiction; Female friendship -- Fiction; Terminally ill -- Fiction; Adoption -- Fiction; Forgiveness -- Fiction